OBLIGATION TO PROVIDE FOOD SAFETY GUARANTEE BY BUSINESS PLAYERS TO CONSUMERS - Yeti Kurniati (SEAN Institute, 2023)
The problem of food safety in Indonesia already has a legal basis that regulates it, namely Law Number 18 of 2012 concerning Food, and Law Number 8 of 1999 concerning Consumer Protection, which requires businesses to ensure food safety so as not to cause harm to consumers. The purpose of this research is to find out and analyse the obligation to provide food safety guarantees by business actors to consumers. This study uses normative legal research, because it is carried out by examining secondary data, so that the specification of the research used is analytical descriptive, with a normative juridical approach, namely research conducted by examining secondary data. The secondary data was obtained by means of a literature study, then to draw conclusions from the results of the research, a qualitative juridical analysis was used. Based on the results of the study, the obligation to provide food safety guarantees by business actors to consumers based on Law Number 18 of 2012 concerning Food in conjunction with Law Number 8 of 1999 concerning Consumer Protection has not been implemented optimally by business actors, so that it has not provided enough protection for consumers, due to the fact that there are still cases of distribution of food that does not meet food safety standards, thus harming consumers.